2010
DOI: 10.1007/s00421-010-1672-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of energy expenditure estimates from the Actiheart and Actical physical activity monitors during low intensity activities, walking, and jogging

Abstract: Combining accelerometry with heart rate monitoring has been suggested to improve energy estimates, however, it remains unclear whether the single, currently existing commercially available device combining these data streams (Actiheart) provides improved energy estimates compared to simpler and less expensive accelerometry-only devices. The purpose of this study was to compare the validity of the heart rate (HR), accelerometry (ACC), and combined ACC/HR estimates of the Actiheart to the ACC estimates of the Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 31 publications
2
43
0
2
Order By: Relevance
“…Various acceierometers have been developed and studied in the past decade for intra-and inter-device reliability and validity [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Previously, our lab conducted similar analyses comparing the Actical® and Actiheart® devices to indirect calorimetry [25].…”
Section: Introductionmentioning
confidence: 95%
“…Various acceierometers have been developed and studied in the past decade for intra-and inter-device reliability and validity [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Previously, our lab conducted similar analyses comparing the Actical® and Actiheart® devices to indirect calorimetry [25].…”
Section: Introductionmentioning
confidence: 95%
“…6,7 The ACT provided valid resting energy expenditure (REE) estimation compared to indirect calorimetry for normal to overweight adults, 8 but discrepancies were observed for EE during short PA periods. 7,9 In a mechanical set-up, the ACT presented a good intra-instrument reliability (coefficient of variation (CV) = 0.5%). 10 Despite its wide use, the ability of ACT to evaluate with accuracy the daily TEE has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that accelerometers underestimate EE as the linearity between counts and aerobic intensity cannot always be assumed at moderate to high velocities 36 . Previous studies observed that the accelerometer component of the combined monitor presents a poor performance compared to other hip worn equipment, particularly at higher intensities during level walking and level jogging 37 . Therefore, the accuracy of accelerometer models from combined sensing may be limited due to the position of the monitor on the sternum 38 .…”
Section: Discussionmentioning
confidence: 99%